1 / 20

340 likes | 808 Views

7.7 Operations on Functions. Composition of Functions. A new way of writing Operations with functions. Adding Subtracting Multiplication Division . Given. Find . Given. Find . Given. Find . Given. Find . Given. Find . Given. Find . Given. Find . Given. Find .

Download Presentation
## 7.7 Operations on Functions

**An Image/Link below is provided (as is) to download presentation**
Download Policy: Content on the Website is provided to you AS IS for your information and personal use and may not be sold / licensed / shared on other websites without getting consent from its author.
Content is provided to you AS IS for your information and personal use only.
Download presentation by click this link.
While downloading, if for some reason you are not able to download a presentation, the publisher may have deleted the file from their server.
During download, if you can't get a presentation, the file might be deleted by the publisher.

E N D

**7.7 Operations on Functions**Composition of Functions**A new way of writing Operations with functions**Adding Subtracting Multiplication Division**Given**Find**Given**Find**Given**Find**Given**Find**Given**Find**Given**Find**Given**Find**Given**Find**Given**Find**Composition of Functions**Combining two functions into one function. Where the answers to one function is the input to the other function. Given two Functions. f(x) = 2x + 1 g(x) = x – 3 f(g(x))=2(x – 3)+1 f(g(x))=2x – 6+1= 2x - 5 Where ever there is an x, put the other function**Composition of Functions**Given two Functions. f(x) = 2x + 1 g(x) = x – 3 f(g(x))=2(x – 3)+1 f(g(x))=2x – 6+1= 2x – 5 g(f(x))=(2x + 1) – 3 = 2x - 2**Composition of Functions“The Books Notation”**Given two Functions. f(x) = 2x + 1 g(x) = x – 3 f(g(x))=2(x – 3)+1 [f○ g](x) f(g(x))=2x – 6+1= 2x – 5 [f○ g](x)= 2x - 5 g(f(x))=(2x + 1) – 3 = 2x - 2 [g ○ f ](x) = 2x - 2**Find [ f ○ g](x) and [ g ○ f ](x) for x = -2**f(x) = 3x2 – x + 4; g(x) = 2x – 1 [ f ○ g](x) find g(-2) = 2(-2) – 1 = -5 find f(-5)**Find [ f ○ g](x) and [ g ○ f ](x) for x = -2**f(x) = 3x2 – x + 4; g(x) = 2x – 1 [ f ○ g](x) find g(-2) = 2(-2) – 1 = -5 find f(-5) = 3(-5)2 – (-5) + 4 =3(25) + 5 + 4 =75 + 5 +4 = 84**Find [ f ○ g](x) and [ g ○ f ](x) for x = -2**f(x) = 3x2 – x + 4; g(x) = 2x – 1 [ g ○ f](x) find f(-2) = 3(-2)2 – (-2) + 4 =3(4) + 2 + 4 =12 + 2 + 4 = 18 find g(18) =**Find [ f ○ g](x) and [ g ○ f ](x) for x = -2**f(x) = 3x2 – x + 4; g(x) = 2x – 1 [ g ○ f](x) find f(-2) = 3(-2)2 – (-2) + 4 =3(4) + 2 + 4 =12 + 2 + 4 = 18 find g(18) = 2(18) - 1 =36 - 1 =35**Homework**Page 387 – 388 # 17, 20, 31, 32, 35 – 43 odd**Homework**Page 387 – 388 # 18, 21, 33, 36 – 44 even

More Related